La hipertensión arterial y diabetes asociada al autocuidado en adultos mayores del grupo amigos dulces del Hospital Isidro Ayora - Loja. - González Toledo, Katherine Andrea (2017)
Arterial hypertension, which is characterized by the increase in normal blood pressure, and diabetes is a metabolic disorder that causes elevated amounts of sugar in the blood. These two frequent chronic illnesses affect senior adults, who represent a third part of all hospital admissions. According to reports of World Health Organization, chronic diseases are the cause of death of an estimated 36 million people each year. The main aim of this descriptive research was to determine self-care methods for hypertension and diabetic patients who are part of the "Dulces Amigos" group in the Isidro Ayora Hospital of the city of Loja. The study sample comprised 120 people. An interview, which applied a Self-Care Agency Appreciation Scale, was implemented. The senior adults who were interviewed were 83.3% women and 17.5% men between ages 44 and 86 years old. Housewife was the most common occupation with 61.7% and retired with 7.5%. The relationship between body mass index and cardiovascular risk reflected that 34 % of the pre-obese women and 10% of men with obesity type I were at high risk of developing cardiovascular complications. In general, self-care capacity was considered as average, with 94%. A deficit of self-care practices regarding treatment management and complications derived from the disease were identified among the study group. These could therefore be more closely coupled with a lack or absence of physical activity and unhealthy eating habits, which led to an increase in cardiovascular complications. KEY WORDS: High blood pressure, diabetes, self-care practices, elderly.